Advances in agronomy. - Sparks, Donald L., 1953- (Advances in agronomy ;, 2018)
"Advances in Agronomy continues to be recognized as a leading reference and first-rate source for the latest research in agronomy. Each volume contains an eclectic group of reviews by leading scientists throughout the world. As always, the subjects covered are rich, varied, and exemplary of the abundant subject matter addressed by this long-running serial. Includes numerous, timely, state-of-the-art reviews on the latest advancements in agronomyFeatures distinguished, well recognized authors from around the worldBuilds upon this venerable and iconic review seriesCovers the extensive variety and breadth of subject matter in the crop and soil sciences"--